Development of a home‐based auditory training to improve speech recognition on the telephone for patients with cochlear implants: A randomised trial. (9th April 2017) - Ihler, F.; Blum, J.; Steinmetz, G.; Weiss, B.G.; Zirn, S.; Canis, M.
Abstract : Objectives: Speech recognition on the telephone poses a challenge for patients with cochlear implants (CIs) due to a reduced bandwidth of transmission. This trial evaluates a home‐based auditory training with telephone‐specific filtered speech material to improve sentence recognition. Design: Randomised controlled parallel double‐blind. Setting: One tertiary referral centre. Participants: A total of 20 postlingually deafened patients with CIs. Main outcome measures: Primary outcome measure was sentence recognition assessed by a modified version of the Oldenburg Sentence Test filtered to the telephone bandwidth of 0.3‐3.4 kHz. Additionally, pure tone thresholds, recognition of monosyllables and subjective hearing benefit were acquired at two separate visits before and after a home‐based training period of 10‐14 weeks. For training, patients received a CD with speech material, either unmodified for the unfiltered training group or filtered to the telephone bandwidth in the filtered group. Results: Patients in the unfiltered training group achieved an average sentence recognition score of 70.0%±13.6% (mean±SD) before and 73.6%±16.5% after training. Patients in the filtered training group achieved 70.7%±13.8% and 78.9%±7.0%, a statistically significant difference ( P =.034, t 10 =2.292; two‐way RM ANOVA/Bonferroni). An increase in the recognition of monosyllabic words was noted in both groups. The subjective benefit was positive for filtered and negative for unfiltered training. Conclusions: Auditory training with specifically filtered speech material provided an improvement in sentence recognition on the telephone compared to training with unfiltered material.